City-Forschungsdefizite und Thesen zu den ökonomischen und politischen Bedingungen der Citybildung, am Beispiel von Göttingen - von Frieling, Hans-Dieter (ERDKUNDE, 1980)
The paper critically analyses the two most important concepts of city research of German-language geography: those of economic regionalism and of functionalistic-social geography. A conceptual gap and deficit in the explanation of city formation appears to be the omission of two aspects, i.e. the separation from the questions first of the economic patterns of commodity distribution under capitalism, and, secondly, of the mechanisms and aims of political intervention. Three examples from Göttingen serve to illustrate the investigation of the effects of concentration tend encies in the retail trade, of trade cycles and of town planning interventions to revive the city centre upon the process of urban growth.